Peran Kimia Medisinal dalam Pengembangan Obat Antikanker Berbasisi Senyawa Alam: Tinjauan Literatur - Saeful Amin; Rosi Rosidah; Agneiva Hasna Nabilah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to comprehensively review the role of medicinal chemistry in the development of anticancer drugs derived from natural compounds through a qualitative literature review of eight recent scientific articles. The methodology involved selecting articles based on strict inclusion and exclusion criteria from reputable scientific databases, followed by systematic analysis to elucidate the contributions of medicinal chemistry in the identification, isolation, and structural modification of bioactive compounds. Findings reveal that medicinal chemistry plays a pivotal role in enhancing the affinity of natural compounds toward cancer targets while minimizing adverse side effects. Structure-activity relationship (SAR) approaches and computational techniques such as molecular docking and virtual screening have proven effective in accelerating the discovery and optimization of anticancer drug candidates. Optimized natural compounds exhibit antiproliferative activity, apoptosis induction, and angiogenesis inhibition across various cancer cell types, which are critical mechanisms in cancer therapy. However, significant challenges include the inconsistent availability of natural raw materials and the complexity of synthesizing these compounds on an industrial scale. Therefore, multidisciplinary collaboration among organic chemistry, pharmacology, and bioinformatics is essential to expedite the development of safe and effective natural compound-based anticancer drugs. This study provides a comprehensive overview of the potential and challenges in natural product-based anticancer drug development, emphasizing the importance of integrating modern technologies in medicinal chemistry to support future cancer therapy innovations.